India In the Way of Viksat Bharat@ 2047 - Sandeep. G. Tiwari, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
In the present context since 2014 government takes various initiatives inform of E-Governance has simplified a citizen interface with the government. to ensure closeness with government the government thrive to ensure benchmarking of service quality. The central government e-governance model has benefited in bringing transparency and openness to government process. To achieve the ends of Viksit Bharat @20247 it adopted of e- version 7.0 has created paperless offices in all departments in the central secretaries. In 2023, the Centralized Public Grievances Redress and Monitoring System (CPGRAMS)helped redress 21 lakh citizen grievances. In 2024 with three months from January to March it helped 9.5 lakh citizens to redress their problems. the best manifestation of Maximum Governance Minimum Government policy is a digitally empowered citizens and digitally transformed institution which is essential for development and speed disposal of public affairs.
Keywords: Structural Adjustment; Entrepreneurship; Intensive Manufacturing; Power security; Green Revolution